2016
DOI: 10.1016/j.geoderma.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Straw mulching is not always a useful post-fire stabilization technique for reducing soil erosion

Abstract: Mulching is increasingly employed to stabilize burnt areas, making necessary to elucidate where and how it should be used. The effects of mulching and the efficiency of two straw application strategies in reducing nutrient losses were evaluated in a steep area (burnt with moderate severity) with twelve experimental plots split into three sets: control burnt plots (BS), burnt plots with straw mulching in narrow bands along the contour lines (NM, global dose 800 kg ha !1) and in wide bands (WM, global dose 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…According to previous studies, 61−63 the application of fire retardant can have long-term effects on the P concentrations in the affected ecosystem. For example, Fernandez et al 63 found that 10 years after the application of fire retardant, the soil-available P concentration was 3 times higher than that in burned soils with no fire retardant application.…”
Section: Discussionmentioning
confidence: 72%
“…According to previous studies, 61−63 the application of fire retardant can have long-term effects on the P concentrations in the affected ecosystem. For example, Fernandez et al 63 found that 10 years after the application of fire retardant, the soil-available P concentration was 3 times higher than that in burned soils with no fire retardant application.…”
Section: Discussionmentioning
confidence: 72%
“…In this case, they attributed the low efficiency as a consequence of the low soil erodibility, low rainfall erosivity, and because the mulch strips were located on the top half of the field plots. Curiously, applying very high application rates in the range of 46 to 17 Mg ha -1 with logging slash mulch (Fernández et al, 2007;Prats et al, 2012;Shakesby et al, 1996), did not show a significant effect and the reasons were also linked to the low erodibility of burnt soils, as it was suggested by Fernández-Fernández et al (2016). A priori, under circumstances of low soil erosion rehabilitation treatments are not needed.…”
Section: Soil Erosion Mitigation With Low Mulch Application Ratesmentioning
confidence: 93%
“…For instance, in pine forests of Central Eastern Spain, Lucas-Borja et al ( 2018) measured lower infiltration rates when soil is not saturated compared to unburned and untreated forest areas, especially in the dry seasons. Fernández-Fernández et al (2016) stated that mulching is not effective in reducing soil erosion and subsequent loss of nutrients; in an experiment carried out in North-Western Spain, these authors showed that the reduction in soil erosion was due to moderate precipitation rather than mulching, and the concentration of some elements in sediments led to problems for vegetation growth and soil health. Moreover, the use of straw, which is commonly used as mulch material, is not always suitable in forest areas, since biomass transport from agricultural sites may be expensive; moreover, these vegetal residues often contain agro-chemicals and parasites, and thus development of non-native vegetation and diseases to forest plants are possible (Bento-Gonçalves et al 2012).…”
Section: Introductionmentioning
confidence: 99%